2024
DOI: 10.1021/jacs.3c12894
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-Enabled Dearomative [2π + 2σ] Cycloaddition of Phenols

Subhabrata Dutta,
Donghyeon Lee,
Kristers Ozols
et al.

Abstract: Dearomative photocycloaddition of monocyclic arenes is an appealing strategy for comprehending the concept of “escape from flatland”. This brings the replacement of readily available planar aromatic hydrocarbon units with a 3D fused bicyclic core with sp 3-enriched carbon units. Herein, we outline an intermolecular approach for the dearomative photocycloaddition of phenols. In order to circumvent the ground-state aromaticity and to construct conformationally restrained building blocks, bicyclo[1.1.0]butanes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The aniline ring could be doubly or triply substituted, leading to densely substituted polycyclic products 27-36. For the symmetrical substrates derived from 2,6-dimethylaniline, 3,5-dimethylaniline, and 2,4,6-trimethylaniline, good to excellent yields were obtained despite the steric hindrance (27)(28)(29). For the non-symmetrical substrates derived from 2,3-dimethylaniline, 2,5-dimethylaniline, and 3,4-dimethylaniline, poor to moderate regioselectivities were observed (30)(31)(32)(33)(34)(35).…”
Section: Substrate Scope Studymentioning
confidence: 99%
“…The aniline ring could be doubly or triply substituted, leading to densely substituted polycyclic products 27-36. For the symmetrical substrates derived from 2,6-dimethylaniline, 3,5-dimethylaniline, and 2,4,6-trimethylaniline, good to excellent yields were obtained despite the steric hindrance (27)(28)(29). For the non-symmetrical substrates derived from 2,3-dimethylaniline, 2,5-dimethylaniline, and 3,4-dimethylaniline, poor to moderate regioselectivities were observed (30)(31)(32)(33)(34)(35).…”
Section: Substrate Scope Studymentioning
confidence: 99%
“…Ring systems, especially small and strained ring systems with a double bond or with a bridged bond, hold high-profile importance in transformations that generate bioisosteric systems. Recent works from Brown and our group , demonstrated that a high energy-containing molecule, bicyclo[1.1.0]­butane (Δ E = 66.3 kcal/mol), could be efficiently engaged in [2π+2σ]-photocycloadditions giving rise to highly sought-after, yet complex sp 3 -rich units. Given the influence of saturated isosteres as target molecules in rational drug design, the demand for expanding its chemical space promises to unravel new exit vectors, potency, pharmacological properties, and physiological assessments (Scheme B) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hoz and co-workers postulated the existence of a radical cation intermediate, arising from single-electron oxidation, in the bromination of bicyclo[1.1.0]­butane analogs . Despite these discoveries, the synthetic potential of bicyclo[1.1.0]­butyl radical cations has been severely underexplored, with nonselective nucleophilic addition being the only transformation demonstrated for these intermediates. We therefore determined to assess the feasibility of employing single-electron oxidation via photoredox catalysis as a strategy to access alternative bicyclo[1.1.0]­butane reactivity.…”
Section: Introductionmentioning
confidence: 99%